Étimos gregos e latinos na formação de termos da medicina em Língua Portuguesa - Volpe, Andrea Sampaio (2015)
This dissertation, in regard to Portuguese language field, has as its theme the study of the etymon (word root) of the Greek and Latin languages employed on a more frequent basis in the medical discursive domain. The objectives are to contribute to the studies at the Etymology field, aiming at increasing the expressive capacity as well as the degree of accuracy in the use of medical terminology of Portuguese language upon the Greek and Latin etymon knowledge. For that purpose, the most frequent terms of the Dermatology, Cardiology and Oncology specialities have been looked up in three dictionaries, in order to gain a broader understanding of their morphosemantic elements (lexemes, prefixes and suffixes), enabling the deduction of their meanings grounded on the etymological knowledge. This study has been predicated on the basis of theoretical studies developed in Terminology and Lexicology (Mario Viaro, Lídia Almeida Barros, Maria Tereza Biderman, Maria da Graça Krieger e Maria José Finatto) on the principles of the Portuguese Etymology and Morphology (Celso Cunha e Lindley Cintra; Antônio Sandmann). The obtained results indicated that: a) the Greek and Latin lexemes present a high degree of transparency in relation to their etymological meanings; therefore, facilitating the language users comprehension; b) the highest productivity in the etymon lies in the affixes, that is, there is a degree of polysemy in each of them, which justifies the semantic opacity in relation to the lexemes; c) as to the medical specialities, the scientific term presented a higher transparency in relation to their eponym. The main contribution of this study is, therefore, that the knowledge of etymological values presented in every morphic element of a term is paramount for the mastery of its signification